Methods of teaching foreign languages in non-classical secondary schools (the latter half of the 19th — early 20th centuries) - Goncharenko, Nataliia (My University, 2015)
In order to develop new, more effective foreign language education media and methods and complete the task of ensuring proper acquisition of foreign languages by students of secondary educational institutions, it is important to appeal to the history of domestic educational theory and practice, in particular as regards substantiation of inclusion of foreign languages in the content of school education, their teaching priorities tracking, analysis of languages teaching organization, forms and methods of such activities and a number of other factors, which enables to avoid admitted mistakes, track the dynamics of the educational area development, identify efficient ways of teaching foreign languages in today’s school education. Для розробки нових, ефективніших засобів та методів навчання іноземним мовам і виконання завдання забезпечення належного засвоєння іноземних мов учнями середніх навчальних закладів важливо звернутися до історії вітчизняної освітньої теорії та практики, зокрема щодо обґрунтування включення іноземних мов до змісту шкільної освіти, відстеження пріоритетів їх викладання, аналізу організації викладання мов, форм і методів такої діяльності та низки інших факторів, що дозволяє уникнути допущених помилок, відстежити динаміку розвитку освітньої галузі, визначити ефективні шляхи викладання іноземних мов у сучасній шкільній освіті.
Keywords: шкільна освіта; school education; іноземна мова; foreign language